THE OVERLAY BRICK METHOD: AN ATTEMPT TO REDUCE THE ORGANIC WASTE FROM HOME - Eva Utami Durahman; Aulia Arifbillah Anwar; Zakiyah Ismuwardani (Community Development Journal : Jurnal Pengabdian Masyarakat, 2025)
The household organic waste management often becomes a major challenge in society, especially in urban areas. The insufficient waste management system can cause environmental problems such as soil and water pollution that can threaten public health. This community service program aims to introduce and implement the overlay brick composting method as an innovative and sustainable solution in organic waste management. This method was chosen because it is simple, efficient, and can be adapted by communities with limited space and resources. The implementation of the program includes socialization, training, and assistance to the community in Perum Panorama Bumi Pasalakan 1, Cirebon Subdistrict. The results of the program showed a significant increase in community knowledge regarding the importance of organic waste management and the application of the overlay brick method. However, at this stage, changes are still limited to understanding, and have not created new habits in waste management. In conclusion, this program has succeeded in increasing public awareness and has the potential to encourage sustainable practices in the future with further assistance.